Kendala dalam Mengajar Pendidikan Agama Islam di Kelas - muriyanto muriyanto (CENDEKIAWAN, 2019)
Education of Islamic Religion is an subject which must be submitted/sent by at formal school of goodness go to school to have Country status and also school have private sector status to. Hence with Education of Islamic Religion submitted/sent by in formal school since Elementary School expected by student will be more know and comprehend better Teaching Islam and become base or foundation of protege x'self. However in its road;street to become student to be able to know and comprehend Islam teaching all that we do not conceive, because all that is done/conducted in education institute do not as easy as which is conceived and surely have constraint in course of learning to teach. From background of writer wish to know what becoming constraint in teaching Education of Islamic Religion in SMP Negeri 1 Karanganom Klaten. Target of this research is researcher wish to know what becoming way to overcome and constraint in study of Education of Islamic Religion in SMP Country 1 Karanganom. Method of Peneltian which is utilized in this research for example observation method, method of interview, documentation method, is analysing data qualitative is obtained data by thinking to obtain;get truth, namely by way of berfikir 1) Deductively Is 2) Inductive 3) Comparability. After writer collect required datas and analysing him hence writer can take conclusion Constraint faced in teaching Education of Islamic Religion in SMP Negeri 1 Karanganom Klaten for example : 1) Constraint of student 2) Constraint of school 3) Incoming constraint of old fellow or family for example 4) Constraint of society. Effort conducted By Teacher In Overcoming Constraint Teach Education of Islamic Religion in SMP Country 1 other Karanganom Klaten atara with: A teacher Education of Islamic Religion do not differentiate among/between student one with is other, teacher always give motivation, learn bersaha give duty either through self-supporting and also grouply, Teacher Education of Islamic Religion always invite cooperation learn the other, delivering pupil sponsor at least each;every intake of raport, Inviting to society around and committee go to school to each other both of the same student to be always berlajar when hour learn, teacher Education of Islamic Religion have never hopelessly and full of patience in running process learn to teach and give motivation to student, performing a religious activity. Effort conducted By Teacher In Overcoming Constraint Teach Education of Islamic Religion in SMP Negeri 1 Karanganom Klaten other atara with: A teacher Education of Islamic Religion do not differentiate between student one with is other, teacher always give motivation, learn bersaha give duty. After teacher Education of Islamic Religion try to overcome constraint teach Education of Islamic Religion hence can be obtained by achievement learn Education of Islamic Religion all class student 8C SMP Country 1 Karanganom Klaten earn 100% above KKM .